Bayesian Evidence Accumulation in Experimental Mathematics: A Case Study of Four Irrational Numbers. Issue 3 (3rd July 2018) - Gronau, Quentin F.; Wagenmakers, Eric-Jan
ABSTRACT: Many questions in experimental mathematics are fundamentally inductive in nature. Here we demonstrate how Bayesian inference—the logic of partial beliefs—can be used to quantify the evidence that finite data provide in favor of a general law. As a concrete example we focus on the general law which posits that certain fundamental constants (i.e., the irrational numbers π, e, , and ln 2) are normal; specifically, we consider the more restricted hypothesis that each digit in the constant's decimal expansion occurs equally often. Our analysis indicates that for each of the four constants, the evidence in favor of the general law is overwhelming. We argue that the Bayesian paradigm is particularly apt for applications in experimental mathematics, a field in which the plausibility of a general law is in need of constant revision in light of data sets whose size is increasing continually and indefinitely.